Smoked Fish Business Development Strategy in Banyuasin Regency, South Sumatera Province - Miskiyah, Neneng; Lupikawaty, Marieska; Aprianti, Siska; Andriyani, Titi (Universitas KH. Abdul Chalim Mojokerto, 2024)
Business development is carried out to improve quality and competitiveness to obtain more profits. Analysis of Strengths, Weaknesses, Opportunities, and Threats can help Panca Jaya smoked fish business to analyze how business development strategies must be implemented and appropriate because in carrying out this business Panca Jaya experiences ups and downs in this business. The method used is SWOT analysis and SWOT matrix. The results showed that Panca Jaya's smoked fish business was in the type I quadrant, where this position indicated that the smoked fish business was in strong condition and had many opportunities. The right strategy in developing the Panca Jaya smoked fish business is to utilize product quality which can be used as a superior commodity by utilizing abundant raw materials. Sungai Rengit Village, Banyuasin Regency can become one of the largest smoked fish business centers in the province of South Sumatra.